ISLAM BERKEMAJUAN DALAM PERSPEKTIF MUHAMMADIYAH: ANALISIS HISTORIS DAN KONSEPTUAL TERHADAP GERAKAN TAJDID DI INDONESIA - Rahman, Nur Amalina Abdul; Nurhayati, St; Wahyuni, Mardiah; Rondhiyah, Siti (STKIP Pesisir Selatan, 2026)
The concept of Progressive Islam represents one of Muhammadiyah’s significant intellectual contributions as a manifestation of its tajdid (renewal) movement in responding to social, cultural, and civilizational changes in the modern era. This study aims to analyze the historical development of Progressive Islam within Muhammadiyah, examine the conceptual foundations of Muhammadiyah’s tajdid movement, and explain the relevance of Progressive Islam to the development of Islamic education in Indonesia. This research employs a qualitative approach using a library research method with historical and conceptual perspectives. Data were collected from scholarly literature, official Muhammadiyah documents, academic books, and relevant national and international journal articles. Data analysis was conducted through content analysis and conceptual analysis of the collected sources. The findings reveal that Progressive Islam emerged from Muhammadiyah’s tajdid movement, which is rooted in the teachings of the Qur’an and Sunnah, and evolved into a paradigm of Islamic renewal that integrates religious purification (purification) and social dynamization (social transformation). The novelty of this study lies in its historical and conceptual synthesis of the relationship between Progressive Islam and Muhammadiyah’s tajdid movement.